Vertebral Body Replacement With an Anchored Expandable Titanium Cage in the Cervical Spine: A Clinical and Radiological Evaluation. Issue 1 (7th October 2020) - Yusupov, Natan; Siller, Sebastian; Hofereiter, Johann; Boehm, Heinrich Karl; Fuetsch, Manuel; Tonn, Joerg-Christian; Zausinger, Stefan
Abstract: BACKGROUND: Expandable cervical cages have been used successfully to reconstruct the anterior spinal column. OBJECTIVE: To perform clinical and radiological evaluation of vertebral body replacement with an anchored expandable titanium cage in the cervical spine after single-level and 2-level corpectomies. METHODS: Between 2011 and 2017, 40 patients underwent a single-level (N = 32) or 2-level (N = 8) anterior corpectomy and fusion using an anchored expandable vertebral body replacement cage. Clinical and radiological data at admission, postoperatively, and at 3- and 12-mo follow-up were retrospectively analyzed. Clinical assessment was performed via standardized neurological evaluation, Odom score, and McCormick classification. Radiological assessment was performed via evaluation of sagittal profile, postoperative position, fusion, and subsidence rates. RESULTS: Mean last follow-up was 14.8 ± 7 mo. Overall clinical and myelopathy-related improvements were shown directly after operation and at last follow-up. A stable centralized positioning of cages was achieved in 37 patients (93%). A mild ventral (>1.5 mm) malplacement was noted in 3 patients (7%) without clinical consequences. Sagittal alignment and preoperative cervical kyphosis improved significantly (7.8° gain of lordosis) and remained stable. Mean preoperative height of operated segments increased by 10 mm postoperatively and remained stable. Fusion rate in non-neoplastic patients and subsidence rate at last follow-up comprised 87.5% and 17.8%. With exception of 1 patient suffering from severe osteoporosis and cage subsidence, no patient needed additional secondary stabilization. CONCLUSION: Anterior corpectomy and fusion by an expandable anchored titanium cage with anchor screws without additional instrumentation resulted in overall clinical improvement and radiological anterior column support, achieving significant and reliable restoration of the physiological sagittal cervical profile.